Subminiature eddy-current transducer for detect violations in welded joints of steel - Malikov, Vladimir; Ishkov, Alexey (AIP conference proceedings, 2022)
The article provides the results of designing a flaw detection unit aimed at studying high-strength steels. Welding joints of transformer tanks made of high-strength low carbon steel were used as the subject matter of the study. This type of material was chosen due to its extra-low carbon content, making it possible to apply methods of eddy-current non-destructive testing. To take direct measurements, a scanning unit, which included a probe based on the eddy current principle and having three circuits assembled on a 81NMA ferrite core, was designed and brought to an optimal state. The unit was tested on samples with model continuity flaws (cracks and holes). Moreover, the modeling of corrosion flaws in welding joints was carried out as part of the study.